Size, composition and distribution of human resource for health in India: new estimates using National Sample Survey and Registry data. Issue 4 (27th May 2019) - Karan, Anup; Negandhi, Himanshu; Nair, Rajesh; Sharma, Anjali; Tiwari, Ritika; Zodpey, Sanjay
Abstract : Objectives: We provide new estimates on size, composition and distribution of human resource for health in India and compare with the health workers population ratio as recommended by the WHO. We also estimate size of non-health workers engaged in health sector and the size of technically qualified health professionals who are not a part of the health workforce. Design: Nationally representative cross-section household survey and review of published documents by the Central Bureau of Health Intelligence. Setting: National. Participants: Head of household/key informant in a sample of 101 724 households. Interventions: Not applicable. Primary and secondary outcome measures: The primary outcome was the number and density of health workers, and the secondary outcome was the percentage of health workers who are technically qualified and the percentage of individuals technically qualified and not in workforce. Results: The total size of health workforce estimated from the National Sample Survey (NSS) data is 3.8 million as of January 2016, which is about 1.2 million less than the total number of health professionals registered with different councils and associations. The density of doctors and nurses and midwives per 10 000 population is 20.6 according to the NSS and 26.7 based on the registry data. Health workforce density in rural India and states in eastern India is lower than the WHO minimum threshold of 22.8 per 10 000 population. More than 80% of doctors and 70% of nurses and midwives are employed in the private sector. Approximately 25% of the currently working health professionals do not have the required qualifications as laid down by professional councils, while 20% of adequately qualified doctors are not in the current workforce. Conclusions: Distribution and qualification of health professionals are serious problems in India when compared with the overall size of the health workers. Policy should focus on enhancing the quality of health workers and mainstreaming professionally qualified persons into the health workforce.